PENGARUH RISIKO PERUSAHAAN DAN KONDISI MAKRO EKONOMI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN ASTRA GRUP INTERNASIONAL - Elsa Fitri Amran; Patria Nagara; Mia Emita Putri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This study aims to determine the effect of systematic risk and macroeconomic conditions on firm value. The sampling technique used was purposive sampling, with a sample of 42 observations during the observation period. The data source used is secondary data. The type of data used is quantitative data in the form of financial statements of Astra International Group companies from 2011 to 2017. The analysis technique used is descriptive statistical analysis, classical assumption test using normality test, multicollinearity test and heteroscedasticity test, multiple linear regression analysis and hypothesis testing using partial test (t), simultaneous test (f) and determination (R2). Data processing methods use SPSS version 16.0 and Microsoft Excel 2010. The results of the analysis show that systematic risk has a significant effect on the value of the company with a significant value of 0.005, while inflation has no significant effect on the value of the company with a significant value of 0.845. Simultaneously or together systematic risk and inflation have a significant effect on firm value with a significant value of 0.018. R2 value of 0.186 can be interpreted that 18.6% of the company's value variable is explained by the company's risk variables and inflation, while the remaining 81.4% is explained by other factors outside of this research variable.